Initial electric field changes of lightning flashes in tropical thunderstorms and their relationship to the lightning initiation mechanism - Ahmad, Mohd Riduan; Mohammad Sabri, Muhammad Haziq; Periannan, Dinesh; Abd. Aziz, Mohamad Zoinol Abidin; Mohd Esa, Mona Riza; Abdul‑Malek, Zulkurnain; Lu, Gaopeng; Zhang, Hongbo; Cooray, Vernon; Williams, Earle R.; Al-Kahtani, Ammar Ahmed; Ab. Kadir, Mohd Zainal Abidin (Elsevier B.V, 2019)
In this paper, the key finding is that all the examined first classic Initial Breakdown (IB) pulses in tropical flashes within the reversal distance were found to be initiated by a clearly detectable Initial E-field Change or IEC (45 –CG, 32 normal IC, and 3 IC initiated by +NBE). The durations of IECs for both –CG and IC flashes in tropical storms were longer than in Florida storms. On the other hand, for the magnitudes of the E-change, the values were smaller compared to Florida storms with averages of 0.30 V/m compared to 1.65 V/m for –CG flashes, and −0.81 V/m compared to −6.30 V/m for IC flashes. The IEC process of lightning flashes in tropical regions took longer to increase the local electric field in order to produce the first IB pulse because of the smaller magnitude of E-change. On the other hand, in Florida storms, the IEC process took a shorter time to increase the local electric field to produce the first IB pulse because of the larger magnitude of E-change. We found that very high frequency (VHF) pulses for tropical thunderstorms started sometime prior to the onset of the IECs. They started between 12.69 and 251.60 μs before the initiation of the IEC for two normal IC flashes. The first two VHF pulses were detected alone without narrow IB pulses (fast antenna and slow antenna records) or any pulses from the Bfield and dE/dt records. Furthermore, the VHF pulses for three IC flashes initiated by +NBEs were also detected before the onset of the IEC. The IEC started immediately after the detection of the +NBE. It is clear that the IEC is initiated by VHF pulses. It can be suggested that lightning is initiated by Fast Positive Breakdowns or FPBs (which emit strong VHF pulses and large +NBEs) and is followed by several negative breakdowns (weak VHF pulses and/or weak NBE-type pulses) before the IEC started. For the case of normal IC flashes, several weaker VHF pulses (mean values of 41.97 mV and 46.4 mV compared to the amplitudes of the VHF pulses of +NBEs of around 800 mV) were detected before the onset of the IEC. As FPBs can occur with a wide range of VHF strengths and E-change amplitudes, it can be suggested these weak VHF pulses accompanied by narrow IB pulses or weak NBE-type pulses detected before the onset of IEC are actually FPBs followed by negative breakdowns or several attempted FPBs